Developing a new Software for increasing knowledge about nutritional needs during pregnancy. Issue 1 (October 2020) - Sunarti,; Salina,; Tahira,; Syarif, Syafruddin; Ahmad, Mardiana; Manapa, Esther Sanda; Jibril,; Usman, Andi Nilawati
Abstract: This study aimed to increase the knowledge of pregnant women about nutritional needs during pregnancy through an Android-based learning media. This study was an experimental study that intends to innovate in the form of an application called Mattampu in pregnant women for all trimesters to increase their knowledge about nutrition during pregnancy. Research sites are the Kanjilo Health Center and Pallangga Health Center in Gowa Regency as long as one month. Measurement of knowledge is carried out twice, namely before and after the provision of education with the application. Before providing education, training was held in advance on how to use the application by the research team. Knowledge of nutrition of pregnant women regarding nutrition during pregnancy at all trimester levels shows that the category is less before education was given through the application of mattampu, and after that, the knowledge of pregnant women at all trimester levels increases to be good. Android-based educational application is able to improve knowledge about nutrition in mothers both in the first, second, and third trimesters.